Spatial typologies and structural characteristics of Jiangnan water town settlements: a “water system–human settlement” perspective - Yang, Zhirong; Wang, Haisong; Kharchenko, Anastasiia (Frontiers in Earth Science, 2025)
The diversity and heterogeneity of the water network environment in the Jiangnan region have fostered highly distinctive water town settlement spaces. Scientific research on the interactions between water system environments and human settlement spaces is of great significance to the high-quality development of urban-rural integration in the Yangtze River Delta. However, current academic research on the spatial patterns of Jiangnan water town settlements under the influence of “water system-human settlement” coupling remains unsystematic. Therefore, this study takes the Eco-Green Integrated Development Zone (EGIDZ) of the Yangtze River Delta—located in the core area of Jiangnan water towns—as a case study, and uses Geographic Information System (GIS) software combined with the landscape pattern index analysis method to study the spatial typologies and structural characteristics of the “water system-human settlement” coupling in 29 towns within EGIDZ. The study reveals the following. 1) The settlement spaces within the EGIDZ of the Yangtze River Delta generally exhibit an agglomeration pattern characterized by ‘single-core large-scale aggregation with multi-core small-scale dispersion,’ among which linear settlements (including low-density and medium-density ones) have the widest distribution, accounting for 45.2%. 2) The water system environment has a significant impact on the spatial forms and characteristics of settlements in the region; these variations in the pattern of Jiangnan water networks determine the basic type characteristics of settlement spaces (point-like, linear, clustered). 3) Jiangnan water town settlements are constantly evolving alongside natural environments and human activities. The natural environment, especially the water system environment, determines the spatial distribution of early settlements, while human activity factors such as agricultural production and infrastructure construction drive the evolution and development of settlement spatial structures. This study further clarifies the inherent order of commonalities and differences in the spatial typologies and structural characteristics of settlements in Jiangnan water towns, providing a reference framework for future policies on protecting distinctive settlements in “new Jiangnan water towns” and methods for landscape construction.